Development of a Multimodal Analgesia Protocol for Perioperative Acute Pain Management for Lower Limb Amputation - Roberta De Jong; Alexander J. Shysh (Pain Research and Management)
Multimodal analgesia may include pharmacological components such as regional anesthesia, opioid and nonopioid systemic analgesics, nonsteroidal anti-inflammatories, and a variety of adjuvant agents. Multimodal analgesia has been reported for a variety of surgical procedures but not yet for lower limb amputation in vasculopathic patients. Perioperative pain management in these patients presents a particular challenge considering the multiple sources and pathways for acute and chronic pain that are involved, such as chronic ischemic limb pain, postoperative residual limb pain, coexisting musculoskeletal pain, phantom limb sensations, and chronic phantom limb pain. These pain mechanisms are explored and a proposed protocol for multimodal analgesia is outlined taking into account the common patient comorbidities found in this patient population.